Effect of Natural Deep Eutectic Solvents and Conventional Solvents on Extraction Yield, Antioxidant Activity, and Toxicity of Peperomia pellucida(L.) Kunth - Saini, Aniza; Benjamin, Mohammad Amil Zulhilmi; Rusdi, Nor Azizun; Abdul Aziz, Ahmad Hazim; Mohd Azrie Awang, (Malaysian Journal of Science, 2025)
Peperomia pellucida (L.) Kunth, commonly known as ‘Sirih Cina,’ is a botanical plant recognised for its traditional application in various therapeutic contexts due to its bioactive compounds. Despite its potential benefits, its properties are sometimes underappreciated. The choice of solvent extraction significantly influences its biological properties. This research investigates the impact of diverse solvents on the extraction yield, antioxidant activity, and toxicity of P. pellucida leaf extracts. The selected solvents include natural deep eutectic solvents (NADES), distilled water, methanol, ethanol, and ethyl acetate. The extraction of P. pellucida leaves was conducted using an ultrasonic water bath apparatus. The aluminium chloride colorimetric assay was employed to determine the total flavonoid content (TFC), while the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was used to assess antioxidant activity. Moreover, the toxicological assessment of P. pellucida leaf extracts was performed using the brine shrimp lethality assay (BSLA) to determine LC50 (lethal concentration 50) values. NADES emerged as the most efficient solvent for extraction, yielding the highest extraction yield (17.39 ± 0.03%) and DPPH scavenging activity (83.31 ± 0.03%), while demonstrating non-toxicity in the BSLA (LC50 = 1597.62 µg/mL). Although NADES ranked third in terms of TFC, a moderate correlation between TFC and DPPH suggests that factors beyond TFC influence antioxidant activity. Overall, NADES exhibited antioxidant activity and showed non-toxicity towards brine shrimp. Therefore, NADES is a suitable solvent for exploring the medicinal potential of P. pellucida leaves as a source for therapeutic applications.